Peran Sistem Informasi Manajemen Peserta Didik dalam Optimalisasi Efisiensi Kerja Bidang Kesiswaan - Haryanto, Edy (Global Education Journal, 2023)
Management Information Systems (MIS) are necessary for effectiveness and efficiency, especially in modern technological developments. Proper SIM management is one of the essential things in maintaining and even developing an educational institution. This is the basis for conducting research at MI Darul Ulum Bantaran, with students whose academic achievements are pretty good. This research aims to determine information services at MI Darul Ulum Bantaran for the 2022/2023 academic year and implementation in educational services at MI Darul Ulum Bantaran for the 2022/2023 academic year. This type of research is descriptive with a qualitative approach with three data collection techniques: observation, documentation, and interviews. This research shows that the implementation of SIM in improving educational services at MI Darul Ulum Bantaran has been carried out well. Based on the research results, it was found that the implementation of SIM at MI Darul Ulum Bantaran, Mulia, has been running following existing guidelines. Education services at MI Darul Ulum Bantaran have two forms of service, namely: (1) essential services (curriculum services, student services, public relations services, infrastructure services) and (2) auxiliary services (library services, information services, health, and security services), SIM implementation at MI Darul Ulum Bantaran has been running well and follow the guidelines set by the ministry of religion, to improve education services.